FACTOR OF CHINA IN EVOLUTION OF THE INDIAN APPROACH TO THE INDO-PACIFIC REGION - A. V. Kupriyanov (Сравнительная политика)
The idea of the Indo-Pacific was created 12 years ago and quickly became the subject of fierce discussions among experts and politicians. Over the years, several Indo-Pacific concepts partially coinciding partially contradicting each other have been formed. The article is devoted to the description and analysis of the evolution of the Indian concept of the Indo-Pacific. It discusses the main directions of Indian strategic thought on the concept and demonstrates the difference in approaches to the Indo-Pacific within the Indian expert community. There were three views in total: anti-Chinese whose supporters called for a departure from a policy of neutrality and for the alliance with the United States, Japan and Australia; critical whose supporters denied the value of the concept of Indo-Pacific; and practical whose supporters were focused on the development of economic relations within the region by expanding contacts with ASEAN, advocating the continuation of the policy of «strategic autonomy» and against a sharp change in the foreign policy. Author believes that the address of the Indian Prime Minister Narendra Modi at the Shangri-La Dialogue in 2018 was the turning point: the head of the Indian government identified there New Delhi's priorities in the implementation of the Indo-Pacific concept. In conclusion, the author describes the current attitude towards the idea of the Indo-Pacific among Indian experts and points out the consequences of a possible Beijing review of the negative attitude towards it.